Synthesis of Micro- and Nanoparticles of Metal Oxides and Their Application for Reinforcement of Al-Based Alloys - S. Vorozhtsov; I. Zhukov; A. Vorozhtsov; A. Zhukov; D. Eskin; A. Kvetinskaya (Advances in Materials Science and Engineering)
This paper presents a comparative analysis of morphology, chemical and phase compositions, and particle size distribution of nanopowders produced by electric explosion of wire (EEW) and plasma-chemical methods. The possibility of introduction of Al2O3 particles into Al alloy by means of a special master alloy and with ultrasonic processing is shown. The improvement of tensile properties of an Al-based composite material reinforced with 0.1 wt% of EEW Al2O3 is demonstrated.